How to Change Young Children's Physical Activity and Sedentary Behavior: Mechanisms of Behavior Change in the INFANT Cluster Randomized Controlled Trial - Kylie D. Hesketh; Konsita Kuswara; Gavin Abbott; Jo Salmon; Jill A. Hnatiuk; Karen J. Campbell (MDPI AG, 2021)
Background: Understanding the mechanisms (mediators) of behavior change is crucial to designing more effective interventions. However, this is rarely reported. This paper investigates the mechanisms that explain the lack of intervention effect on physical activity and the significant effect on television viewing time from an early childhood trial. Methods: Secondary analyses were undertaken of data from a cluster randomized controlled trial. The Melbourne Infant Feeding, Activity and Nutrition Trial (INFANT) was a 15-month group program promoting obesity-protective behaviors from the age of 4 months. Outcomes relevant to the current study were child physical activity (accelerometer), television viewing time (maternal report) and 12 potential mediator scales (maternal report). Linear regression models used the product of coefficients method with a joint significance test. Results: Complete data were from 398 mother-child dyads. Despite weak evidence of an intervention effect on the mother's physical activity knowledge and optimism, there was no effect on children's physical activity, and no clear mechanisms were identified. An intervention effect was observed for the mothers' television knowledge (unstandardized regression coefficient for a path (a) = 0.34, 95% confidence interval (CI95) = 0.22, 0.45), with weak evidence for maternal efficacy (a = 0.11, CI95 = −0.02, 0.24) and the use of television (a = −0.10, CI95 = −0.22, 0.01). The intervention impact on television knowledge explained 75% of the difference between the intervention and control groups in children's television viewing. Conclusions: In the very early childhood period, as mothers are commencing their parenting journey, improving their behavioral knowledge appears to be the biggest contributor to reducing child television viewing, constituting a relatively simple strategy that could be implemented across clinical and public health settings. In contrast, it remains unclear what mechanisms may increase physical activity levels in this age group.